IMPLEMENTASI KEBIJAKAN VAKSINASI COVID-19 DI KABUPATEN CIREBON (STUDI KASUS KECAMATAN PLERED KABUPATEN CIREBON DAN KECAMATAN DEPOK KABUPATEN CIREBON) - Doni Nugroho; Subhan Haris; Agus Irfan (Jurnal Ilmu Sosial dan Ilmu Politik (JISIP), 2022)
In recovering conditions due to the Covid-19 pandemic, through the President's direction that Indonesia must immediately carry out herd immunity or group immunity. For this reason, the Covid-19 vaccination was carried out so that the government mobilized the TNI and Polri and involved the regional government as the organizer of the Covid-19 vaccination. The Cirebon Regency Government is making efforts to achieve good Covid-19 vaccination. Plered and Depok are the sub-districts that have been one of the successes of the Covid-19 vaccination in Cirebon Regency. The purpose of the study was to determine the implementation of the Covid-19 vaccination policy in Plered and Depok Districts, Cirebon Regency. The study used a qualitative descriptive approach. The data collection techniques used primary data and secondary data. The informant selection technique in this study used purposive sampling and snowball techniques. The results of the research are First, the communication carried out by the organizers of the Covid-19 vaccination is carried out systematically and massively, whether it is transmission communication, consistent communication. However, in clear communication, there are a few obstacles, namely the change in the schedule for the implementation of the Covid-19 vaccination, which makes Covid-19 vaccination participants confused. Second, the resources for the implementation of the Covid-19 vaccination are adequate, sufficient and of good quality. Third, Disposition in the implementation of the Covid-19 vaccination is carried out according to established regulations. The Cirebon District Health Office did not recruit a team of volunteers to carry out the Covid-19 vaccination. Fourth, the bureaucratic structure in the implementation of the Covid-19 vaccination uses the structure of the Cirebon District Health Office.Dalam pemulihan kondisi akibat pandemi Covid-19 melalui arahan Presiden bahwa Indonesia harus segera melakukan herd immunity atau kekebalan kelompok. Untuk itu, dilakukan vaksinasi Covid-19 sehingga pemerintah mengerahkan TNI dan Polri serta melibatkan pemerintah daerah sebagai peyelenggara vaksinasi Covid-19. Pemerintah Kabupaten Cirebon melakukan upaya guna capaian vaksinasi Covid-19 baik. Kecamatan Plered dan Kecamatan Depok merupakan kecamatan yang menjadi salah satu keberhasilan vaksinasi Covid-19 di Kabupaten Cirebon. Tujuan penelitian adalah untuk mengetahui implementasi kebijakan vaksinasi Covid-19 di Kecamatan Plered dan Kecamatan Depok Kabupaten Cirebon. Penelitian menggunakan pendekatan deskripsi kualitatif. Adapun teknik pengumpulan data menggunakan data primer dan data sekunder. Teknik pemilihan informan dalam penelitian menggunakan teknik purposive sampling dan teknik snowball. Hasil penelitian yaitu Pertama, Komunikasi yang dilakukan oleh penyelenggara vaksinasi Covid-19 dilaksanakan secara sistematis dan massive  baik itu komunikasi transmisi, komunikasi konsisten. Namun, dalam komunikasi kejelasan sedikit ada kendala yaitu terdapatnya perubahan jadwal pelaksanaan vaksinasi Covid-19 membuat binggung peserta vaksinasi Covid-19. Kedua, Sumber daya dalam pelaksanaan vaksinasi Covid-19 memadai, mencukupi dan berkualitas baik. Ketiga, Disposisi dalam pelaksanaan vaksinasi Covid-19 dijalankan sesuai peraturan yang telah ditetapkan. Dinas Kesehatan Kabupaten Cirebon tidak merecruit tim relawan untuk pelaksanaan vaksinasi Covid-19. Keempat, Struktur birokrasi dalam pelaksanaan vaksinasi Covid-19 menggunakan struktur dari Dinas Kesehatan Kabupaten Cirebon.